2020
DOI: 10.3847/1538-4357/ab899d
|View full text |Cite
|
Sign up to set email alerts
|

Streaming Instability in Turbulent Protoplanetary Disks

Abstract: The streaming instability for solid particles in protoplanetary disks is reexamined assuming the familiar alpha (α) model for isotropic turbulence. Turbulence always reduces the growth rates of the streaming instability relative to values calculated for globally laminar disks. While for small values of the turbulence parameter, α < 10−5, the wavelengths of the fastest growing disturbances are small fractions of the local gas vertical scale height H, we find that for moderate values of the turbulence paramet… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
101
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(107 citation statements)
references
References 100 publications
4
101
2
Order By: Relevance
“…An alternative possibility is that these dust clumps result from the streaming instability (Youdin & Goodman 2005;Youdin & Johansen 2007) that tends to enhance the concentration of solids. Although our numerical resolution of ≈ 15 grid cells per scale-height is probably insufficient to resolve the streaming instability whose most unstable wavelength is typically ≈ ℎ𝐻, recent work (Chen & Lin 2020;Urmurhan et al 2020) has shown that in turbulent discs with 𝛼 ≈ 10 −3 , the most unstable wavelength might be shifted toward scales as large as 𝐻 (Johansen et al 2007;Umurhan et al 2020). In that case, our numerical resolution would be sufficient to witness the SI operating.…”
Section: Possible Formation Of Dusty Clumpsmentioning
confidence: 90%
“…An alternative possibility is that these dust clumps result from the streaming instability (Youdin & Goodman 2005;Youdin & Johansen 2007) that tends to enhance the concentration of solids. Although our numerical resolution of ≈ 15 grid cells per scale-height is probably insufficient to resolve the streaming instability whose most unstable wavelength is typically ≈ ℎ𝐻, recent work (Chen & Lin 2020;Urmurhan et al 2020) has shown that in turbulent discs with 𝛼 ≈ 10 −3 , the most unstable wavelength might be shifted toward scales as large as 𝐻 (Johansen et al 2007;Umurhan et al 2020). In that case, our numerical resolution would be sufficient to witness the SI operating.…”
Section: Possible Formation Of Dusty Clumpsmentioning
confidence: 90%
“…Over recent years, several works have shown that the generation of planetesimals via the SI in a smooth disk profile remains difficult. First, a large amount of solid material (Z > 0.02)larger than the typical ISM value -has to be provided in a single dust species of a particular Stokes number (Yang et al 2017;Johansen et al 2014), leaving a relatively narrow range of parameters (Umurhan et al 2020;Chen & Lin 2020), even more narrow when including the effect of turbulence (Jaupart & Laibe 2020). However such favorable conditions -a low amount of turbulence and a narrow range in mass distribution of large grains -is not expected from dust evolution models (Brauer et al 2008;Birnstiel et al 2011).…”
Section: Regions Of Planetesimal Formationmentioning
confidence: 99%
“…Recent studies emphasized again the importance of the level of gas turbulence when determining where the SI can operate (Jaupart & Laibe 2020; Umurhan et al 2020). So far, most simulations have been performed in local box simulations, and only recently did globally unstratified simulations come into use (Kowalik et al 2013;Mignone et al 2019), confirming the main characteristics of the SI.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, a distribution of grains has been shown to strongly impede the growth of the streaming instability in the low-dust-to-gasratio regime (Krapp et al 2019), while turbulence and/or viscosity can significantly limit the applicability of the instability in many scenarios (e.g. Squire & Hopkins 2018b;Umurhan, Estrada & Cuzzi 2019;Chen & Lin 2020;Jaupart & Laibe 2020;Krapp et al 2020;Zhuravlev 2020). Our models could, nonetheless, prove useful as the basis for more complex models of instabilities in systems with distributions of grain sizes, while turbulence, viscosity, or dust diffusion could likely be straightforwardly added, if desired (for example, viscosity will impede the growth of modes below some scale).…”
Section: The Philosophy Of This Articlementioning
confidence: 99%